Activity-Based Teaching and Learning Approach and Students’ Academic Performance: Evidence from Among Stakeholders from Barekese District Ashanti Region of Ghana - Apenuvor, Theophilus; Gbadago, Frank Yao; Ankomah, Kwadwo; Anthony, Agnes Fafa (International Journal of Educational Studies, 2021)
In this study, the authors explored the level of awareness and views on the activity-based approach to teaching and learning (ABTLA) in enhancing skills, competency and academic performance among students and other stakeholders from Senior High Schools (SHS) and Colleges of Education (COE) in Barekese District of Ashanti Region of Ghana. A survey involving 510 various stakeholders was conducted within the Barekese District of Ashanti Region of Ghana, using sets of a self-administered structured questionnaire. The study revealed that the Ghanaian stakeholders of second cycle and COEs are highly aware of ABTLA and its potency for enhancing skills, competency and academic performance among students. Policy implications and further future research directions were provided.